Request Strategies in the American TV Series Full House - Yemima Febriani; Sharifah Hanidar (Lexicon, 2019)
This research aims to analyze the request strategies used in an American TV Series entitled Full House season 7 episodes 1-12. The main characters are family members from three different age groups (adult, teenager, and children). This research attempts to see if there is any difference on the choice of request strategies used by the three age groups. Blum-Kulka and Olshtain’s (1984) theory on request directness level is used to classify the requests. Relative power and social distance are also studied to see how they influence the characters in making their requests. The results show that mood derivable is the most frequent strategy used by all age groups. Specifically, direct request is highly used by the adult age groups. On the other hand, indirect request is mostly used by the younger age groups. The results also show that all age groups tend to use direct strategy when the social distance is negative. However, when the social distance is positive, the choice of strategy depends on the authority of the speaker.